Perezhivanie, Emotions and Subjectivity Advancing Vygotsky’s Legacy - Fleer, Marilyn; González Rey, Fernando; Veresov, Nikolai (Perspectives in Cultural-Historical Research, 2017)
VIII, 265 p. 8 illus.